2017
DOI: 10.1111/joid.12097
|View full text |Cite
|
Sign up to set email alerts
|

Child Life Specialists’ Evaluation of Hospital Playroom Design: A Mixed Method Inquiry

Abstract: This study uses the expertise of child life specialists to identify which elements support child life goals for hospitalized children. This study can be used to inform those interested in the optimal design of hospital playrooms. Ninety child life specialists were surveyed using a photograph methodology showing five actual child life playrooms from different hospitals. The participants were asked the following: rate each playroom on 14 dimensions; describe what was liked best about each playroom; and finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…When the children in this study were unable to interact with others in the playroom, they found that situation to be 'boring' as demonstrated in the findings. However, the current practice in supporting play in palliative care is usually based on providing physical space and equipment for the children to use (Weinberger et al, 2017), and therefore, designing the services has to take into consideration facilitating social connectivity that meets children's need for social interaction and enjoyment of play.…”
Section: Discussionmentioning
confidence: 99%
“…When the children in this study were unable to interact with others in the playroom, they found that situation to be 'boring' as demonstrated in the findings. However, the current practice in supporting play in palliative care is usually based on providing physical space and equipment for the children to use (Weinberger et al, 2017), and therefore, designing the services has to take into consideration facilitating social connectivity that meets children's need for social interaction and enjoyment of play.…”
Section: Discussionmentioning
confidence: 99%
“…Children experience substantial psychological benefits when engaging in outdoor play in natural environments (Fjørtoft, 2001;Chawla, 2007;McCurdy et al, 2010). Only recently have researchers studied biophilic interior spaces and present findings showing the importance of natural features in playrooms on cognitive development, social-emotional development, and overall wellbeing (Swank and Shin, 2015;Weinberger et al, 2017). In order to later assess the biophilic quality in urban residential playrooms and the psychological effects that children experience in a low biophilic playroom and a high biophilic playroom, assessing the methodological soundness of a measure that identifies and quantifies biophilic design features in these spaces is needed.…”
Section: Discussionmentioning
confidence: 99%
“…From a therapeutic perspective, playrooms are optimal indoor environments for combining play-therapy and biophilia to the child's benefit. Weinberger et al (2017) surveyed child life specialists at a hospital to evaluate which elements within hospital playrooms are of importance to children. Biophilic elements were of high value to specialists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…True biophilic design needs to mimic this natural complexity. In a recent study, greater biophilic variety was associated with experts' selection of the “best” playroom (Weinberger, Butler, McGee, Schumacher, & Brown, ). This preference for nature‐based variety suggests that organized complexity can be exhibited through the thoughtful application of a variety of nature‐based features.…”
Section: Nature Benefitsmentioning
confidence: 99%